1998
DOI: 10.1111/j.1600-0765.1998.tb02208.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transforming growth factor beta one (TGF‐β1) on wound healing, with or without barrier membranes, in a Class II furcation defect in sheep

Abstract: The purpose of this study was to analyse the effect of TFG-beta 1 on wound healing in standardized Class II furcation defects of 48 mandibular second premolar teeth in 24 sheep. The experimental design included a control group (carrier only, 25% pluronic F-127), and 2 experimental groups: group A (80 micrograms/ml TGF-beta 1 + carrier) and group B (80 micrograms/ml TGF-beta 1 + carrier covered with a barrier membrane). Sheep were killed either 2 wk or 6 wk after surgery. Mesiodistal sections of the decalcified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…33,34 Treatment of wounds with nanogram quantities of TGF-, resulted in significant differentiation of structures and a decrease in the size of wound areas. 35,36 Significant proliferation of epithelial cells detected in wounds treated with G-90 by histological analysis was probably a consequence of induced growth factors (EGF, FGF). From our results we conclude that G-90 is a valuable mixture of biologically active macromolecules, that in nanogram quantities increase proliferation of cells, and may therefore accelerate wound healing.…”
Section: Discussionmentioning
confidence: 98%
“…33,34 Treatment of wounds with nanogram quantities of TGF-, resulted in significant differentiation of structures and a decrease in the size of wound areas. 35,36 Significant proliferation of epithelial cells detected in wounds treated with G-90 by histological analysis was probably a consequence of induced growth factors (EGF, FGF). From our results we conclude that G-90 is a valuable mixture of biologically active macromolecules, that in nanogram quantities increase proliferation of cells, and may therefore accelerate wound healing.…”
Section: Discussionmentioning
confidence: 98%
“…Ripamonti et al (1996) reported that doses from 5 to 100 mg of rhTGF-b1 in a collagen matrix carrier provided rather limited bone regenera-tion after 30 days in nonhuman primate critical size calvarial defects. Mohammed et al (1998) evaluated purified monkey TGF-b1 in sheep class II furcation defects and found that at 2 weeks, TGF-b1 plus carrier sites did not differ from carrier controls. At 6 weeks, TGF-b1 plus carrier sites had significantly more bone than carrier alone; nevertheless, in the 6-week TGF-b1 specimens the increase over controls was only 11% of the total defect volume.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers are already trying to establish new treatments to accelerate the regeneration of periodontal tissue by local application of human recombinant cytokines to stimulate proliferation and differentiation into hard-tissue forming cells of undifferentiated mesenchymal cells among periodontal ligament cells. Direct local application of a combination of factors such as platelet-derived growth factor (PDGF) and insulin-like growth factor (IGF)-I [6], bone morphogenetic protein (BMP)-2 [7], [8], transforming growth factor (TGF)-β [9], osteogenic protein (OP)-1 [10] and brain-derived neurotrophic factor (BDNF) [11] to artificial defects in periodontal tissue made in laboratory animals reportedly stimulates and promotes regeneration of regional periodontal tissue. In addition, the efficacy of PDGF-BB plus β-tricalcium phosphate (β-TCP, an osteoconductive scaffold) for periodontal tissue regeneration in human has recently been reported [12].…”
Section: Introductionmentioning
confidence: 99%